Biological control ecology of Tamarixia triozae (Burks) (Hymenoptera: Eulophidae) on Bactericera cockerelli (Šulc) (Hemiptera: Triozidae) : a thesis presented in partial fulfillment of the requirements for the degree of Doctor of Philosophy in Plant Science (Entomology) at Massey University, Manawatū, New Zealand - Chen, Chen (Massey University, 2023)
Tamarixia triozae (Burks) (Hymenoptera: Eulophidae) is an important primary parasitoid of tomato-potato psyllid Bactericera cockerelli (Šulc) (Hemiptera: Triozidae), a serious invasive pest of solanaceous crops. It kills its hosts by both feeding and parasitisation. However, its biological control ecology is still not well known, making it difficult to develop an effective biological control programme using this parasitoid. In this thesis, I investigated adult circadian rhythms, diets, life history strategies, and host selection behaviour in T. triozae. My results show that most emergence occurred in the morning and most mating took place early the next morning. Oviposition only occurred during the daytime, peaking between mid-morning and mid-afternoon while host feeding had three peaks in the early morning, late afternoon, and dawn. Adults fed with honey for four days with no access to hosts or with water or yeast for one day followed by host feeding for three days had similar longevity and lifetime pest killing ability. Adults fed with only water for one day immediately before release had significantly greater intrinsic rate of increase, shorter doubling time, and higher daily fecundity peak. Adults fed with honey or yeast for one day followed by host feeding for three days significantly flattened their daily oviposition curves. T. triozae females could feed on nymphs of all instars but preferred mid-aged ones for feeding. Most parasitisation occurred on older nymphs. Host feeding and parasitism peaked during the first week of female life and declined markedly after two weeks. Parasitoids allocated more fertilised eggs to older and larger nymphs. The oviposition of fertilised eggs peaked when females were four to five days old, with > 90 % of daughters produced during the first half of their life. There was a positive relationship between the host size at parasitisation and parasitoid offspring fitness. The parasitoid behaviours consisted of encounter, evaluation, piercing for feeding, feeding, oviposition probing, and oviposition, and host defence behaviours included body swaying and escaping. Female wasps were more likely to encounter and evaluate older and larger hosts. However, encounter and evaluation did not necessarily translate into feeding and oviposition success. Older nymphs had more resources, thicker integument and stronger defence ability and the opposite was the case for younger ones. The present study provides novel knowledge for development of effective T. triozae mass rearing, shipment, and release programmes for the control of B. cockerelli.
Chapters 2 and 3 are republished with permission: Chen, C., He, X.Z., Zhou, P. et al. Tamarixia triozae, an important parasitoid of Bactericera cockerelli: circadian rhythms and their implications in pest management. BioControl 65, 537–546 (2020). https://doi.org/10.1007/s10526-020-10023-0; and Chen, C., He, X.Z., Zhou, P. et al. Diets for Tamarixia triozae adults before releasing in augmentative biological control. BioControl 67, 297–306 (2022). https://doi.org/10.1007/s10526-022-10136-8.
Keywords: Eulophidae; Behavior; Life cycles; Paratrioza cockerelli; Biological control; Biological pest control agents; 300804 Horticultural crop protection (incl. pests, diseases and weeds)